Coli Surface Antigen 26 Acts as an Adherence Determinant of Enterotoxigenic Escherichia coli and Is Cross-Recognized by Anti-CS20 Antibodies - Cádiz, Leandro; Torres, Alexia; Valdés, Raúl; Vera, Gabriel; Gutiérrez, Daniela; Levine, Myron M.; Montero, David A.; O’Ryan, Miguel; Rasko, David A.; Stine, O. Colin; Vidal, Roberto; Del Canto, Felipe (Frontiers in Microbiology, 2018)
The coli surface antigen 26 (CS26) of enterotoxigenic Escherichia coli (ETEC) had been described as a putative adhesive pilus based on the partial sequence of the crsH gene, detected in isolates from children with diarrhea in Egypt. However, its production and activity as adherence determinant has not been experimentally addressed. The crsH was identified as a homolog of genes encoding structural subunits of ETEC colonization factors (CFs) CS12, CS18 and CS20. These CFs, along with the recently discovered CS30, belong to the γ2 family of pili assembled by the chaperone-usher pathway (CU pili). Further, the complete CS26 locus, crsHBCDEFG, was described in an O141 ETEC strain (ETEC 100664) obtained from a diarrhea case in The Gambia, during the Global Enterics Multicenter Study. Here, we report that CS26 is a pilus of 10nm in diameter, with the capacity to increase the cell adherence of the non-pathogenic strain E. coli DH10B. As for other related pili, production of CS26 seems to be regulated by phase variation. Deletion of crsHBCDEFG in ETEC 100664 significantly decreased its adherence capacity, which was recovered by in trans complementation. Furthermore, CrsH was cross-recognized by polyclonal antibodies directed against the major structural subunit of CS20, CsnA, as determined by Western blotting and immunogold labelling. ETEC CS26+ strains were found to harbor the heat-labile enterotoxin only, within three different sequence types of phylogroups A and B1, the latter suggesting acquisition through independent events of horizontal transfer. Overall, our results demonstrate that CS26 is an adhesive pilus of human ETEC. In addition, cross-reactivity with anti-CsnA antibodies indicate presence of common epitopes in γ2-CFs.